Association between a history of periodontitis and the risk of rheumatoid arthritis: a nationwide, population-based, case–control study. Issue 7 (31st August 2012) - Chen, Hsin-Hua; Huang, Nicole; Chen, Yi-Ming; Chen, Tzeng-Ji; Chou, Pesus; Lee, Ya-Ling; Chou, Yiing-Jenq; Lan, Joung-Liang; Lai, Kuo-Lung; Lin, Ching-Heng; Chen, Der-Yuan
Abstract : Objective: To investigate the association between the risk of rheumatoid arthritis (RA) and a history of periodontitis. Methods: This nationwide, population-based, case–control study used administrative data to identify 13 779 newly diagnosed patients with RA (age ≥16 years) as the study group and 137 790 non-patients with RA matched for age, sex, and initial diagnosis date (index date) as controls. Using conditional logistic regression analysis after adjustment for potential confounders, including geographical region and a history of diabetes and Sjögren's syndrome, ORs with 95% CI were calculated to quantify the association between RA and periodontitis. To evaluate the effects of periodontitis severity and the lag time since the last periodontitis visit on RA development, ORs were calculated for subgroups of patients with periodontitis according to the number of visits, cumulative cost, periodontal surgery and time interval between the last periodontitis-related visit and the index date. Results: An association was found between a history of periodontitis and newly diagnosed RA (OR=1.16; 95% CI 1.13 to 1.21). The strength of this association remained statistically significant after adjustment for potential confounders (OR=1.16; 95% CI 1.12 to 1.20), and after variation of periodontitis definitions. The association was dose- and time-dependent and was strongest when the interval between the last periodontitis-related visit and the index date was <3 months (OR=1.64; 95% CI 1.49 to 1.79). Conclusions: This study demonstrates an association between periodontitis and incident RA. This association is weak and limited to lack of individual smoking status.